Trade imbalances and multilateral trade cooperation - Juan Marchetti; Michele Ruta; Robert Teh (Center for Economic Studies and ifo Institute (CESifo), 2012)
Rising current account and merchandise trade imbalances marked the years before the global financial and economic crisis. These imbalances either contributed to or precipitated the crisis and to the extent that they create systemic risks, it is desirable that they be reduced. There are many factors related to macroeconomic, structural, exchange rate and financial policies that contributed to the imbalances. The inability to manage these issues at the international level reflects the coherence gap in global governance. This paper examines the contribution that the WTO can make in its three areas of activities - negotiations, rule-making and dispute settlement - to deal with trade imbalances and with the main factors leading to them, including exchange rate misalignments. First, market opening efforts in services, including in the area of financial services, can reduce policy-related distortions and market imperfections in surplus countries that lead to the build-up of unsustainable imbalances. Second, in the context of a broad international effort to coordinate macroeconomic, exchange rate and structural policies to deal with the roots of imbalances (the first-best solution), there is a general efficiency argument that could be made for the use of WTO-triggered trade actions to enforce cooperative behaviour towards rebalancing. Absent this first-best response, trade rules alone would not provide an efficient instrument to compensate for the weaknesses in international co-operation in macroeconomic, exchange rate and structural policies.
Keywords: F13; F32; F55; 330; global imbalances; multilateral trade rules; international governance; Zahlungsbilanzungleichgewicht; Leistungsbilanz; Internationale Handelspolitik; WTO-Regeln